Effect of the minority ions on the ICRF heating of fusion plasmas - Pavlenko, I.V.; Girka, I.O.; Leviga, B.I. (Вопросы атомной науки и техники, 2012)
Additional plasma heating, for example ICRF (Ion Cyclotron Range of Frequencies) heating, allows heating only a group of the fuel particles which will initiate the thermonuclear fusion reaction. But the ICRF heating scenarios are sensitive to the small fractions of the impurities, the fusion products and the minority ions. Therefore the optimization of the fraction ratio between the fuel ions and other ion components is required. It takes into consideration the effect of the ion components on the heating mechanism, the power interchange between the plasma components and the power loss channels from the confinement volume. The conditions of transferring from minority heating regime to the mode conversion one is studied for the reactor relevant D-T experiments. Дополнительный нагрев плазмы, например, ВЧ-нагрев, позволяет нагревать только группу частиц топлива, которые будут инициировать термоядерную реакцию. Но сценарии ВЧ-нагрева чувствительны к малым фракциям примесей, продуктов реакции и ионов малой добавки. Поэтому требуется оптимизация процентного соотношения между ионами топлива и прочими ионами. Она должна принимать во внимание влияние ионных компонентов на механизмы нагрева, обмен энергией между компонентами плазмы и каналы ухода энергии из объёма удержания. Условия перехода от режима нагрева ионов малой добавки к режиму конверсии мод изучаются для перспективных экспериментов с дейтериево-тритиевой плазмой. Додаткове нагрівання плазми, наприклад, ВЧ-нагрівання, дозволяє нагрівати тільки групу частинок палива, які будуть ініціювати термоядерну реакцію. Але сценарії ВЧ-нагрівання є чутливими до малих фракцій домішок, продуктів реакції та іонів малої добавки. Тому є необхідність в оптимізації відсоткового співвідношення між іонами палива та іншими іонами. Оптимізація повинна приймати до уваги вплив іонних компонентів на механізми нагрівання, обмін енергією між компонентами плазми та канали втрати енергії з об’єму утримання. Умови переходу від режиму нагрівання іонів малої добавки до режиму конверсії мод вивчаються для перспективних експериментів з дейтерієво-тритієвою плазмою.